Gaya Dakwah Husein Ja'far Al-Hadar dalam Menyebarkan Islam kepada Generasi Z - Khafi, Muhammad Abdul; Kaisan, Muhammad Zaidan; Zahwa, Raihanna; Anwar, Amanda Novia; Fadhil, Abdul (TSAQOFAH, 2025)
This research aims to analyze the style of Husein Ja'far Al-Hadar's da'wah in conveying the teachings of Islam to Generation Z. The research method used is qualitative with a literature study approach and netnography on digital platforms such as YouTube. The research findings show that Husein Ja'far succeeded in reaching Generation Z through an inclusive, relevant communication approach, and utilizing social media effectively. With a relaxed style, light-hearted narration, and a focus on contemporary issues, he is able to convey the message of Islam in a way that is easily accepted by the younger generation. The study also reveals challenges and opportunities in digital da'wah, such as the need for credible and innovative content in order to compete in the information age. The results of this study provide insight into the importance of adapting da'wah methods to meet the characteristics and needs of today's generation.